2024
DOI: 10.1021/acs.jmedchem.3c01845
|View full text |Cite
|
Sign up to set email alerts
|

Series of Desloratadine Platinum(IV) Hybrids Displaying Potent Antimetastatic Competence by Inhibiting Epithelial–Mesenchymal Transition and Arousing Immune Response

Ming Zhang,
Yan Chen,
Zhifang Liu
et al.

Abstract: Metastasis is the major obstacle to the survival of cancer patients. Herein, a series of new desloratadine platinum(IV) conjugates with promising antiproliferative and antimetastatic activities were developed and evaluated. The candidate complex caused significant DNA damage and stimulated mitochondrial apoptosis through the Bcl-2/Bax/caspase3 pathway. Then, it suppressed the epithelial–mesenchymal transition (EMT) process in tumors effectively through NMT-1/HPCAL1 and β-catenin signaling. Subsequently, the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In view of these stimulating facts and as a continuation of our interest in developing novel antitumor agents, it was of great interest for us to design novel platinum(IV) conjugates with EMT suppressing and immunoregulating properties. Isoquinoline alkaloids are an important group of natural bioactive products, which display a wide variety of pharmacological properties such as antimicrobial, antibacterial, antifungal, antitumor, etc. Canadine (CND) as a unique isoquinoline alkaloid shows much potential as antiproliferative and antimetastasis agents. The mechanism detection revealed that CND was potent in inhibiting the EMT process, , inhibiting inflammation, and further modulating immune responses. , Accordingly, we intended to incorporate CND into the platinum(IV) system as a functional ligand with the aim of discovering novel platinum(IV) agents with potent antiproliferative and antimetastatic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these stimulating facts and as a continuation of our interest in developing novel antitumor agents, it was of great interest for us to design novel platinum(IV) conjugates with EMT suppressing and immunoregulating properties. Isoquinoline alkaloids are an important group of natural bioactive products, which display a wide variety of pharmacological properties such as antimicrobial, antibacterial, antifungal, antitumor, etc. Canadine (CND) as a unique isoquinoline alkaloid shows much potential as antiproliferative and antimetastasis agents. The mechanism detection revealed that CND was potent in inhibiting the EMT process, , inhibiting inflammation, and further modulating immune responses. , Accordingly, we intended to incorporate CND into the platinum(IV) system as a functional ligand with the aim of discovering novel platinum(IV) agents with potent antiproliferative and antimetastatic properties.…”
Section: Introductionmentioning
confidence: 99%